2021
DOI: 10.3390/separations8090143
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Selected Mycotoxins in Maize from North-West South Africa Using High Performance Liquid Chromatography (HPLC) and Other Analytical Techniques

Abstract: Contamination of foods by mycotoxins is linked to various health and economic implications. This study evaluated the incidence of mycotoxins in commercial and small-scale maize and evaluated potential health risks for consumers based on South African and international regulations. The sensitivity/specificity of HPLC over other analytical methods used was also ascertained. In total, 100 maize samples were analyzed using immuno-affinity column for extraction and clean-up, thin layer chromatography (TLC), HPLC, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…The fumonisin levels were significantly higher in maize (101-53,863 µg kg −1 ) as compared with the fumonisin levels in porridge (0.2-20 µg kg −1 ) and faecal samples (0.3-464 µg kg −1 ). Further research indicated that a high proportion of the fumonisins is destroyed in the process of making porridge from the maize [90]. Altogether, 114 samples from maize grown by rural subsistence farmers in two districts of northern South Africa were analysed for fumonisins during two seasons.…”
Section: Fumonisins In Southern African Countriesmentioning
confidence: 99%
“…The fumonisin levels were significantly higher in maize (101-53,863 µg kg −1 ) as compared with the fumonisin levels in porridge (0.2-20 µg kg −1 ) and faecal samples (0.3-464 µg kg −1 ). Further research indicated that a high proportion of the fumonisins is destroyed in the process of making porridge from the maize [90]. Altogether, 114 samples from maize grown by rural subsistence farmers in two districts of northern South Africa were analysed for fumonisins during two seasons.…”
Section: Fumonisins In Southern African Countriesmentioning
confidence: 99%
“…Implementation of good agricultural practices (GAP), good manufacturing practices (GMP), and hazard analysis and critical control points (HACCP), amongst other measures, have been proposed. The adoption of GAP in the field and during storage, GMP during food processing, and HACCP during food handling and packaging throughout the whole field-to-table chain will go a long way to address the problems caused by fungi and mycotoxins in the food system [121,122].…”
Section: Management Of Food Safety Risks Of Fusarium Mycotoxinsmentioning
confidence: 99%
“…(c) Food handling and packaging includes the use of technologies such as modified atmosphere packaging (MAP), which is a useful technology that involves the use of oxygen (O 2 ) absorbents, storage temperature, and packaging film barrier. MAP can be used to prevent fungal growth and mycotoxin contamination on finished products [122,124] Creating awareness of the importance of adopting GAP, GMP, and HACCP to control (prevention and decontamination) mycotoxin metabolites in the food system will be useful in reducing the risk of mycotoxin exposure to some extent. Mycotoxin control strategies should also include approaches for the diversion of contaminated agricultural products to lower-risk uses.…”
Section: Management Of Food Safety Risks Of Fusarium Mycotoxinsmentioning
confidence: 99%
“…These results prompted researchers in SA to focus on Fusarium mycotoxins. From review, major mycotoxin reports from both the subsistence and commercial farming systems show no significant different except for AFs, where a high incidence of AFs were discovered in maize and other foodstuff from small-scale compared to commercial farms [ 19 ]. This indicates that millions of South Africans from rural settlements are exposed to the effects of mycotoxins on a regular basis.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies on maize are conducted as multi-mycotoxins research. Some of these have revealed the absence of contamination with aflatoxins (AFs) in SA commercial maize [ 3 , 22 , 23 ], while others have reported their presence [ 12 , 13 , 16 , 19 , 24 , 25 , 26 , 27 , 28 ]. Subsistence farmers in SA and their immediate communities are exposed to dietary AFs in maize, milk, carry-over in animal products, and other processed foods daily.…”
Section: Introductionmentioning
confidence: 99%